African Perspectives on Ethics for Healthcare Professionals (Advancing Global Bioethics,, 2018)
This book focuses on ethical issues faced by a variety of healthcare practitioners across the Anglophone African continent. This important resource contains in-depth discussions of the most salient current ethical issues by experts in various healthcare fields. Each profession is described from both an African and a South African perspective, and thus contributes to dialogue and critical thinking around African ethics and decision-making. In this way the book provides readers with an understanding of the ethical issues at hand in various professions, including the practical implications of the ethical issues and how to address those effectively. This is a beneficial resource for all those involved in the various healthcare professions addressed in this book, including undergraduate students, lecturers, researchers and practitioners across the continent. Simply put, with the dynamic changes and challenges in healthcare across the globe and in Africa, this is an indispensable resource for healthcare practitioners. .